Isolamento de Clostridioides difficile em potros e éguas - Dornelles, Landa Munhoz [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
Clostridioides difficile é importante patógeno nosocomial em humanos e animais. O objetivo deste estudo foi avaliar a ocorrência de C. difficile em potros, éguas e ambiente. Amostras de fezes foram colhidas de potros de até três dias de vida, de suas mães (fezes e úbere), e do ambiente. As amostras foram submetidas a cultivo seletivo para C. difficile. O gene 16S rDNA foi identificado por PCR, assim como os genes codificadores de toxinas (tcdA, tcdB, cdtA/B) e ribotipagem. Amostras de fezes de potros também foram submetidas a qPCR para identificação do gene 16S rDNA e tcdB. A frequência de isolamento foi de 78% em potros, 4% em fezes de éguas, 6% em úbere e 23,53% em ambiente. Em potros, foram obtidos 42 isolados, em sua maioria não toxigênicos (92,9%), com apenas três isolados toxigênicos (RT AI-21/0, e dois novos RTs). De acordo com a qPCR, 81,82% das amostras de fezes foram positivas, com 8,3% de positividade para tcdB. Esse estudo demonstrou alta frequência de isolamento de Clostridioides difficile em potros até três dias de vida em propriedades rurais, com predomínio de isolados não toxigênicos.

Clostridioides difficile is an important nosocomial pathogen in humans and animals. The aim of this study was to evaluate the occurrence of C. difficile in foals, mares, and the environment. Fecal samples were collected from up to three-day-old foals and their dams (feces and udder), and environmental samples were collected. The samples were subjected to selective culture for C. difficile. The 16S rDNA gene was identified via PCR, as were toxin-encoding genes (tcdA, tcdB, cdtA/B) and ribotyping. Foals fecal samples were also subjected to qPCR for detection of the 16S rDNA and tcdB genes. The isolation frequency was 78% in foals, 4% in mares feces, 6% in udder samples, and 23.5% in environmental samples. In foals, 42 isolates were obtained, the majority of which were nontoxigenic (92.9%), with only three toxigenic strains (RT AI-21/0 and two new ribotypes). According to the results of the qPCR analysis, 81.82% of the fecal samples were positive, with 8.3% positive for the tcdB gene. This study revealed a high frequency of Clostridioides difficile isolation in foals up to three days old from Brazilian stud farms, predominantly involving nontoxigenic strains.
Isolation of Clostridioides difficile in foals and mares
Keywords: Potros; Diarreia em potros; Clostridioides difficile; Ribotipagem